Airframe integration for an LH2 hybrid-electric propulsion system. Issue 6 (30th September 2014) - Smith, Howard
Abstract : Purpose: – The purpose of this paper is to explore some of the challenges associated with the integration of an LH2-fuelled advanced hybrid-electric distributed propulsion system with the airframe. The airframe chosen as a case study is an ultra-high-capacity blended wing body configuration. It is designed to represent an A-380 class vehicle but in the 2025-2030 timeframe. The distributed propulsion system is a hybrid-electric concept that utilizes high-temperature superconducting technologies. The focus of the study is the application of LH2 as a fuel, with comment being given to kerosene and LCH4. Design/methodology/approach: – The study consists of a conceptual design developed through the preliminary design phase and part way into the detailed design phase. Findings: – The relationship between passenger capacity and fuel capacity is developed. Some remaining challenges are identified. Practical implications: – The study supports further conceptual design studies and more detailed system studies. Social implications: – The study contributes to the development of more environmentally benign aviation technologies. The study may assist the development of solutions to the peak oil challenge. Originality/value: – The study explores the integration of a number of complex systems into an advanced airframe to an unusual depth of engineering detail.